On the dynamics of photo-electrons in C60. (14th April 2015) - Gao, C-Z; Wopperer, P; Dinh, P M; Suraud, E; Reinhard, P-G
Abstract: We explore photo-electron spectra (PES) and photo-electron angular distributions (PAD) of C60 with time-dependent density functional theory (TDDFT) in real time. To simulate experiments in gas phase, we consider isotropic ensembles of cluster orientations and perform orientation averaging of the TDDFT calculations. First, we investigate ionization properties of C60 by one-photon processes in the range of VUV energies. The PES map the energies of the occupied single-particle states, while the weights of the peaks in PES are given by the depletion of the corresponding level. The different influences can be disentangled by looking at PES from slightly different photon frequencies. PAD in the one-photon regime can be characterized by one parameter, the anisotropy. This single parameter unfolds worthwhile information when investigating the frequency and state dependences. We also discuss the case of multi-photon ionization induced by strong infrared laser pulses in C60 . In agreement with measurements, we find that the PES show a regular comb of peaks separated by the photon energy. Our calculations reveal that this happens because only very few occupied states of C60 near the ionization threshold contribute to emission and that these few states happen to cooperate filling the same peaks. The PAD show a steady increase of anisotropy with increasing photon order.